2003
DOI: 10.1016/s0378-1097(03)00722-5
|View full text |Cite
|
Sign up to set email alerts
|

The glyoxylate bypass ofRalstonia eutropha

Abstract: The glyoxylate bypass genes aceA1 (isocitrate lyase 1, ICL1), aceA2 (isocitrate lyase 2, ICL2) and aceB1 (malate synthase, MS1) of Ralstonia eutropha HF39 were cloned, sequenced and functionally expressed in Escherichia coli. Interposon-mutants of all three genes (vaceA1, vaceA2 and vaceB1) were constructed, and the phenotypes of the respective mutants were investigated. Whereas R. eutropha HF39vaceA1 retained only 19% of ICL activity and failed to grow on acetate, R. eutropha HF39vaceA2 retained 84% of acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
1
30
1
Order By: Relevance
“…One possible explanation for this finding is that, in either mutant, the activity of the other isocitrate lyase enzyme present is capable of compensating for the loss of iclA or iclB. Our data differ from those of a previous study which showed that an iclA mutant of R. eutropha HF39 was unable to grow on acetate as the sole carbon source (60). All glyoxylate cycle mutant strains grew similarly to the wild type in rich media and minimal media containing fructose as the sole carbon source (data not shown), indicating that the growth defect of Re2304 was dependent on the carbon source.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…One possible explanation for this finding is that, in either mutant, the activity of the other isocitrate lyase enzyme present is capable of compensating for the loss of iclA or iclB. Our data differ from those of a previous study which showed that an iclA mutant of R. eutropha HF39 was unable to grow on acetate as the sole carbon source (60). All glyoxylate cycle mutant strains grew similarly to the wild type in rich media and minimal media containing fructose as the sole carbon source (data not shown), indicating that the growth defect of Re2304 was dependent on the carbon source.…”
Section: Resultscontrasting
confidence: 99%
“…Other genes of interest that are upregulated during growth on trioleate include the malate synthase gene aceB (A2217) and the isocitrate lyase genes iclA (A2211) and iclB (A2227), which provides evidence that the glyoxylate bypass plays a role in triacylglycerol metabolism (Table 3). Previous studies have shown that expression of isocitrate lyase is significantly induced when R. eutropha is grown on acetate, in contrast to malate synthase expression (60). Our analysis shows that while malate synthase is upregulated in the presence of trioleate compared to fructose, both isocitrate lyase genes are upregulated to a much greater degree.…”
Section: Resultssupporting
confidence: 43%
See 2 more Smart Citations
“…7) Studies of subfamily 3 ICLs have been limited, and several enzymatic characteristics have been reported only for C. maris, Colwellia psychrerythraea, Acinetobacter calcoaceticus, and Capriavidus nector. [8][9][10][11] A mesophilic bacterium, Azotobacter vinelandii, is known to be capable of nitrogen fixing, and the ratio of oxygen and nitrogen was found to be closely involved in the nitrogen-fixing level and growth of this bacterium. 12) Several properties of A. vinelandii ICL (AvICL) have been studied with a cell-free extract, 13) but the properties of the purified enzyme have not been reported, and the gene encoding the ICL has not been cloned.…”
mentioning
confidence: 99%